Ukraine : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper presents a snapshot of some economic issues for Ukraine. It analyzes risks for the banking sector stability. It investigates Ukraine's real equilibrium exchange rate, drawing chiefly from cross-country panel-data analysis, and the experience of other neighboring East-European countries. The results suggest that Ukraine will likely experience significant upward pressure on the real exchange rate, particularly as it orients itself to the European Union. The paper also uses newly available data to give a broad overview of Ukraine's asset and liability position vis-a-vis the rest of the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet